Stakeholder perceptions of physical literacy: results from a national consultation in England - Duncan, Michael J.; Essiet, Inimfon; Hurter, Liezel; Roberts, William M.; Lewis, Kiara; Goss, Hannah; Morris, Jade L.; Bingham, Daniel D.; O’Brien, Wesley; Barnett, Lisa M.; Shearer, Cara; Daly-Smith, Andrew; et al. (Frontiers in Sports and Active Living, 2024)
Background: There is a lack of evidence of stakeholder perspective and understanding of physical literacy among relevant stakeholders from England. As part of research commissioned by Sport England to develop a physical literacy consensus statement for England, this study presents findings from the first national consultation with stakeholders in England.Methods: One hundred and ninety-three individual stakeholders (50.3%) from education, community sport, national governing bodies of sport, physical activity and sport coaching sectors completed an online survey consisting of fixed item and open ended questions designed to examine their knowledge, understanding, perceptions and practices relating to physical literacy.Responses from stakeholders suggested there was confusion in use of the term physical literacy in practice and confusion regarding the definition of physical literacy. Most respondents suggested they were involved in physical literacy related activity and understood the term. However, when probed the physical literacy related activity they referred to was likely not actually physical literacy related. Understanding of the term physical literacy was inconsistent in general. Stakeholders considered the affective, social, physical and cognitive areas (domains) of learning to be most important for developing a positive relationship with movement, sport and physical activity for life.Conclusions: While stakeholders are aware of the term 'physical literacy' and hold value of it within their practice, there remain key misconceptions relating to what physical literacy is, and debate as to whether any existing definitions truly capture the construct of physical literacy.